A Multi‐Parametric Catalyst Screening for CO2 Hydrogenation to Ethanol. Issue 14 (26th May 2021) - Goryachev, Andrey; Pustovarenko, Alexey; Shterk, Genrikh; Alhajri, Nawal S.; Jamal, Aqil; Albuali, Mohammed; van Koppen, Luke; Khan, Il Son; Russkikh, Artem; Ramirez, Adrian; Shoinkhorova, Tuiana; Hensen, Emiel J. M.; et al.
Abstract: The direct hydrogenation of CO2 to higher alcohols has the potential to turn the main contributor of global warming into a valuable feedstock. However, for this technology to become attractive, more efficient and, especially, selective catalysts are required. Here we present a high throughput study on the influence of different promoters on the CO2 hydrogenation performance of Rh−SiO2 catalysts. Fe and K promoters were found to improve ethanol selectivity at the expense of undesired CH4 . The best‐performing catalyst, with a composition 2 wt.% K, 20 wt.% Fe, and 5 wt.% Rh, displays an EtOH selectivity of 16 % at CO2 conversion level of 18.4 % and CH4 selectivity of 46 %. The combination of different characterization techniques and catalyst screening allowed us to unravel the role of each catalyst component in this complex reaction mechanism. Abstract : Multi‐Parametric Catalyst : Promoted Rh‐based catalysts were used in one‐step CO2 hydrogenation to ethanol. The Fe and K promotion led to an improved ethanol selectivity and drastically reduced CO2 methanation. The optimal catalyst was capable of producing EtOH with the lowest selectivity of S CH4 =46 % at S EtOH =15.9 % and X CO2 =18.4 %. The role of each element was studied by a set of advanced characterization techniques and the structure‐activity relationships were defined.